Penanganan Sanitasi Permukiman Di Kecamatan Magersari Kota Mojokerto - Raditya Anindyajati; Moch. Shofwan (LPPM Universitas Putera Batam, 2023)
Magersari Subdistrict is one of the subdistricts located in Mojokerto City which has a risk area for domestic wastewater, household waste and environmental drainage. The method used in this research is descriptive qualitative with the data collection techniques used in this research namely observation and documentation. The purpose of this study is to find out how much effort the community has made in carrying out sanitation and also the proper handling. The results of the analysis based on IFAS and EFAS calculations show that the matrix quadrant is located in quadrant I. This shows that Magersari District has great strengths and advantages from the internal and external sectors in handling residential sanitation in Magersari District.